ChemInform Abstract: Efficient Microwave‐Assisted Synthesis of N‐(tert‐Butylsulfinyl)imines Catalyzed by Amberlist‐15. Issue 45 (23rd October 2014) - Sanaboina, Chakrapani; Jana, Samaresh; Eppakayala, Laxminarayana
Abstract A general, simple and efficient method for the synthesis of the title compounds by using Amberlite‐15 as a heterogeneous catalyst is reported.